2023
DOI: 10.1186/s12916-023-02838-2
|View full text |Cite
|
Sign up to set email alerts
|

Three tyrosine kinase inhibitors cause cardiotoxicity by inducing endoplasmic reticulum stress and inflammation in cardiomyocytes

Abstract: Background Tyrosine kinase inhibitors (TKIs) are anti-cancer therapeutics often prescribed for long-term treatment. Many of these treatments cause cardiotoxicity with limited cure. We aim to clarify molecular mechanisms of TKI-induced cardiotoxicity so as to find potential targets for treating the adverse cardiac complications. Methods Eight TKIs with different levels of cardiotoxicity reported are selected. Phenotypic and transcriptomic responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…Turning to manual annotations of compound MOA and/or targets, we found that cyclooxygenase inhibitors along with tyrosine kinase receptor inhibitors were the most significant annotations differentiating the various DICT concern categories (Table ); this is plausible given cyclooxygenase inhibition, besides reducing inflammation, can also lead to increased blood pressure while tyrosine kinase receptor inhibition can induce endoplasmic reticulum stress and inflammation in cardiomyocytes . In agreement with this, known targets of prostaglandin endoperoxide synthases (PTGS1 and PTGS2 genes, which encode cyclooxygenases COX-1 and COX-2) could significantly distinguish among most-, less-, and no-DICT concern categories (Table ).…”
Section: Resultssupporting
confidence: 57%
“…Turning to manual annotations of compound MOA and/or targets, we found that cyclooxygenase inhibitors along with tyrosine kinase receptor inhibitors were the most significant annotations differentiating the various DICT concern categories (Table ); this is plausible given cyclooxygenase inhibition, besides reducing inflammation, can also lead to increased blood pressure while tyrosine kinase receptor inhibition can induce endoplasmic reticulum stress and inflammation in cardiomyocytes . In agreement with this, known targets of prostaglandin endoperoxide synthases (PTGS1 and PTGS2 genes, which encode cyclooxygenases COX-1 and COX-2) could significantly distinguish among most-, less-, and no-DICT concern categories (Table ).…”
Section: Resultssupporting
confidence: 57%
“…Turning to manual annotations of compound mechanisms of action and/or targets, we found that cyclooxygenase inhibitors 56 along with tyrosine kinase receptor inhibitors were the most significant annotations differentiating the various DICT concern categories (Table 3); this is plausible given cyclooxygenase inhibition, besides reducing inflammation, can also lead to increased blood pressure 57 while tyrosine kinase receptor inhibition can induce endoplasmic reticulum stress and inflammation in cardiomyocytes. 58 In agreement with this, known targets of prostaglandin endoperoxide synthases (PTGS1 and PTGS2 genes, which encode cyclooxygenases COX-1 and COX-2) could significantly distinguish among most-, less- and no-DICT concern categories (Table 3).…”
Section: Resultssupporting
confidence: 55%
“…Though we did not specifically address the mechanism that stands behind activation of immunoproteasome subunit expression following the incubation with the MKIs, it is well established that non-constitutive proteasome expression is increased in various stress conditions including oxidative stress ( Johnston-Carey et al, 2015 ; Petersen and Zetterberg, 2016 ; Raynes et al, 2016 ; Wang et al, 2023 ). MKIs were demonstrated to induce various types of stress ( Wang et al, 2023 ). Specifically, sorafenib was shown to induce oxidative stress, endoplasmic reticulum stress and inflammation ( Rahmani et al, 2007 ; Wei et al, 2021 ; Wang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…MKIs were demonstrated to induce various types of stress ( Wang et al, 2023 ). Specifically, sorafenib was shown to induce oxidative stress, endoplasmic reticulum stress and inflammation ( Rahmani et al, 2007 ; Wei et al, 2021 ; Wang et al, 2023 ). Regorafenib was also shown to induce endoplasmic reticulum stress ( Sui et al, 2023 ), as well as the oxidative stress in colon cancer cells ( Yu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%